Online Learning Meets Mixed-Reality Immersive Spaces: Result Increased Learning - Carver, Lin B; Atkins, Holly (Advances in Social Sciences Research Journal, 2019)
Online learning in higher education is no longer an anomaly. The majority of American college courses include some digital components, and fully online degree programs are ubiquitous throughout all disciplines. The delivery format of online courses is particularly in line with the needs of the adult learner who often faces challenges of balancing work, family, and graduate coursework. While flexibility is an appealing aspect to online courses, the question of how to engage learners in meaningful, collaborative knowledge-creation remains. Innovative developments in technology provide support in the search for the answer. A small, private university in the southeastern United States employed the use of mixed-reality simulations to increase student-to-student engagement and to encourage the transfer of skills between the classroom and the real-world setting. Students enrolled in an introductory qualitative research course applied the theoretical concepts foundational to conducting effective focus groups through the use of a simulated middle school classroom environment with six student participants (avatars). Using a web conferencing tool that enabled all participants (and the course instructor) to see and be seen during individual focus group sessions, collaborative, shared experiences became the central feature of what students described as an important experience. Innovative tools such as mixed-reality immersive environments provide faculty from a range of disciplines to engage online students in experiences in which the online platform supports and extends meaningful learning.